(untitled) (Indonesian Journal of Counseling and Development, 2023)
This research is predicated on the significance of gratitude as a positive emotion that adolescents need to cultivate in order to build resilience and readiness to face challenges. The objective of this study is to explore the potential of group exercise techniques in fostering gratitude among adolescents. Adolescents are expected to exhibit various positive traits, such as competitiveness, intelligence, self-regulation, self-disclosure, and a heightened sense of gratitude. The data analysis in this study employed the Miles and Huberman model, which consists of three stages: 1) reduction, 2) presentation, and 3) verification. The findings suggest that gratitude is a crucial characteristic in adolescents, and group exercise techniques can potentially enhance this trait. By nurturing gratitude in adolescents, they can achieve psychological well-being and mitigate negative emotions such as anxiety, anger, and sadness